Estudo do tratamento de efluente de lavanderia pelo processo combinado de coagulação/floculação e separação por membranas - Cardoso, Camila de Oliveira (2017)
Industrial laundries wastewaters have in your composition a large amount of dirty that leaving the washed items and chemical additives used during the washing process. In this paper, aiming the treatment of this type of effluent was studied the combined process of coagulation-flocculation (C/F) and membrane separation. Three natural coagulants (Tanfloc POP, Tanfloc SG and Tanfloc SL) were tested in C/F process searching to determine the best color and turbidity removal in the shortest settling time. The statistical analysis and coagulant acquisition cost were decisive in selection of the best natural coagulant. The highest removal of the parameters color (88.7%) and turbidity (92.8%) as well as the lowest cost showed Tanfloc POP coagulant for subsequent testing of Doehlert experimental design. The experimental design results indicated the concentration of coagulant Tanfloc POP equal to 110 mg L-1 and pH of 6.4 as the best experimental condition to obtain the supernatant used in sequential membrane filtration tests. Microfiltration (MF) and ultrafiltration (UF) membranes were tested at pressures 0.6, 1.0 and 1.4 bar in relation to permeate flow. The MF membrane at pressure of 1.4 bar showed the highest value of permeate flow as well as the largest removal of studied parameters. The combined process coagulation/flocculation/membrane was efficient to remove the analyzed parameters, reaching remove of 99.1% to turbidity and 98.4% of color at pressure of 1.4 bar. The permeate obtained in this condition of C/F-MF of combined process was classified in Class 2, 3 and 4 of reuse waters proposed by ABNT-NBR-13969/97 for floors washing, gardens irrigation and flushing toilets.